Avaliação da modulação autonômica cardiovascular e da rigidez arterial de indivíduos com diabetes mellitus tipo 2 - Silva, Claudio Donisete da (Universidade Federal de São Carlos, 2023)
Background: Cardiovascular system problems are widely studied in the population affected by type 2 diabetes mellitus (T2DM), among these problems are those related to cardiovascular autonomic modulation (MAC), accessed through heart rate variability (HRV) blood pressure variability (BPV) and baroreflex sensitivity (BRS) as well as problems related to arterial stiffness (AS). Furthermore, it is known that breathing exerts a great influence on the cardiovascular system and the coupling between these two systems may also be impaired in T2DM patients. Thus, the present thesis aimed to investigate the relationship between MAC and AS and whether cardiorespiratory coupling (CRC) can present damage in the T2DM population. This thesis consists of two studies, presented below: Study 1: Objective: To investigate the existence of an association between AS and BPV in T2DM patients and to verify whether higher levels of AS impact autonomic responses in this population. Methods: 74 individuals with a clinical diagnosis of T2DM participated in the study, of both sexes and aged between 40 and 65 years. These were divided into two groups based on the level of AS identified by the pulse wave velocity (PWV) value, in the AS group (ASG n=13) and in the non-arterial stiffness group (NASG, n=61). AS was assessed by PWV using the SphygmoCor® device with transducers positioned over the right carotid and right femoral arteries and by pulse wave analysis to obtain the augmentation index (AIx) and the augmentation index corrected for a heart rate of 75 beats per minute (AIx@75). BPV was evaluated beat to beat by photo plethysmography using Finometer equipment (Finometer Pro, Finapres Medical Systems). For statistical analysis, Pearson's or Spearman's correlation test was used as appropriate and two-way ANOVA was performed to identify differences between groups. Results: Patients with T2DM showed a significant correlation between AS and BPV index. The mean PWV found when evaluating the whole group was 5.94±1.96 m/s, and when divided into groups the means were ASG 8.90 (8.27-9.85) and NASG 5.20 (4.58-5.97) m/s. In addition, the groups showed differences in heart rate variability and baroreflex sensitivity. Conclusion: In individuals with T2DM, the assessed AS index showed a significant association with BPV. Study 2: Objective: to evaluate the CRC in T2DM patients and healthy individuals and test the hypothesis that this method can provide additional knowledge to the information obtained through HRV, both by linear and non-linear methods. Methods: Individuals diagnosed with T2DM2 (T2DM=32) and a control group with apparently healthy subjects (CON=32) participated in this study. For CRC analysis, the electrocardiogram, non-invasive blood pressure and thoracic respiratory movement were recorded at rest in the supine position and in the standing position after an active postural maneuver. Beat-to-beat series of cardiac period and systolic blood pressure were analyzed with the respiratory movement signal using a traditional non-causal approach, such as the squared coherence function (k2). Two-way mixed-model ANOVA was used to compare groups and post-hoc analysis was performed using Tukey's test. In this T2DM sample, no differences in HRV were observed when compared to the healthy control group, but T2DM patients showed a reduction in resting CRC. Conclusion: We conclude that in patients with T2DM, the ACR, reflected by the squared coherence function, may already be compromised even before the changes in HRV.
Assessment of cardiovascular autonomic modulation and arterial stiffness in type 2 diabetes mellitus patients
Keywords: Sistema cardiovascular; Diabetes Mellitus tipo 2; Frequência cardíaca; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL